Efektivitas Sanksi Pajak Kendaraan Bermotor terhadap Kepatuhan Wajib Pajak Orang Pribadi dengan Tingkat Penghasilan Wajib Pajak sebagai Variabel Pemoderasi di Kabupaten Buleleng - Mahendra, Made Ardi; Dharmawan, Nyoman Ari Surya (Universitas Pendidikan Ganesha, 2021)
In order to get the maximum income from Motor Vehicle Tax, it is necessary to have compliance from the taxpayer itself. The level of taxpayer compliance can be affected by the existence of tax sanctions as a preventive effort to curb and deter taxpayers and tax offenders. However, large accumulated tax sanctions often make people with limited income not paying their obligations. Therefore, this study aimed to investigate the effectiveness of tax sanctions on taxpayer compliance with taxpayer income levels as a moderating variable. This research was a quantitative study which used multiple linear regression analysis method with 100 individual taxpayers as the sample. The data were collected using a closed-ended questionnaire with Likert scale. The results show that motor vehicle tax sanctions provide 12.4% effectiveness on taxpayer compliance, while the income level of taxpayers is not a moderating variable that affects the relationship between tax sanctions and taxpayer compliance.